Markers of Deception in Italian Speech - Spence, Katelyn; Villar, Gina; Arciuli, Joanne (Frontiers in Psychology, 2012)
Lying is a universal activity and the detection of lying a universal concern. Presently, there is great interest in determining objective measures of deception. The examination of speech, in particular, holds promise in this regard; yet, most of what we know about the relationship between speech and lying is based on the assessment of English-speaking participants. Few studies have examined indicators of deception in languages other than English. The world’s languages differ in significant ways, and cross-linguistic studies of deceptive communications are a research imperative. Here we review some of these differences amongst the world’s languages, and provide an overview of a number of recent studies demonstrating that cross-linguistic research is a worthwhile endeavour. In addition, we report the results of an empirical investigation of pitch, response latency, and speech rate as cues to deception in Italian speech. True and false opinions were elicited in an audio-taped interview. A within subjects analysis revealed no significant difference between the average pitch of the two conditions; however, speech rate was significantly slower, while response latency was longer, during deception compared with truth-telling. We explore the implications of these findings and propose directions for future research, with the aim of expanding the cross-linguistic branch of research on markers of deception.